2020
DOI: 10.5937/fme2002383b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and optimization of machining parameters influence on surface roughness in turning AISI 4340 steel

Abstract: This paper focuses on the experimental investigation of machining parameters such as cutting speed, feed rate and depth of cut influence over surface roughness parameters (Ra, Ry and Rt) during turning AISI 4340 steel. Further, in order to achieve smaller surface roughness parameter values, the machining parameters are optimized using Taguchi's technique Signal-to-Noise ratio (S/N ratio). Analysis of Variance (ANOVA) is performed to determine the most contributing factor that influences the surface roughness p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…If there is no combinatory impact, the significance of the first variable is the same regardless of the value of the second factor, and vice versa. The bigger the skew among the components, the greater the interaction among the lines (Deepanraj et al 2020). A interaction implies that the effect of the first variable is dependent on the level of the second factor, and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…If there is no combinatory impact, the significance of the first variable is the same regardless of the value of the second factor, and vice versa. The bigger the skew among the components, the greater the interaction among the lines (Deepanraj et al 2020). A interaction implies that the effect of the first variable is dependent on the level of the second factor, and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…To assess and optimize the welding parameters, the Taguchi methodology, a method for generating process improvements, was employed [25,26]. By choosing the main variables that influence the process [27][28][29] and optimizing the methods to get the best results, these enhancements strive to improve the desirable features and reduce flaws. To examine the variation in the output responses, the input parameters are grouped and clustered in the L9 orthogonal array (OA) order [30,31].…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Balakrishnan Deepanraj et al, [18] conducted experiments on selected process parameters like cutting speed, feed rate, depth of cut to get the surface roughness as an output by using Taguchi L9 OA design on AISI 4340 steel as a workpiece. Therefore, it was observed that the most contribution factor to get surface roughness was feed rate 70.50% and followed by depth of cut (18.54%) and cutting speed (9.15%).…”
Section: Introductionmentioning
confidence: 99%